2019
DOI: 10.48550/arxiv.1905.06374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tame cuspidal representations in non-defining characteristics

Abstract: Let k be a non-archimedean local field of residual characteristic p = 2. Let G be a (connected) reductive group that splits over a tamely ramified field extension of k. We revisit Yu's construction of smooth complex representations of G(k) from a slightly different perspective and provide a proof that the resulting representations are supercuspidal.Moreover, we show that an analogous construction yields smooth, irreducible, cuspidal representations over an arbitrary algebraically closed field R of characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Yu's construction [21] produces a supercuspidal representation π out of the datum Σ. Recently, Fintzen [11] has shown that if the residue characteristic p does not divide the order of the Weyl group, this construction yields all supercuspidal representations of G(F ). 4.2.…”
Section: Review Of Tame and Regular Supercuspidal Representationsmentioning
confidence: 99%
“…Yu's construction [21] produces a supercuspidal representation π out of the datum Σ. Recently, Fintzen [11] has shown that if the residue characteristic p does not divide the order of the Weyl group, this construction yields all supercuspidal representations of G(F ). 4.2.…”
Section: Review Of Tame and Regular Supercuspidal Representationsmentioning
confidence: 99%
“…Although the proof contained no error, it was based on a statement that had been published with a misprint, and was false. A correct proof of Yu's theorem was given more recently by Fintzen [Fi19], in connection with her proof of the fundamental theorem [Fi21] that we have already mentioned several times.…”
Section: Other Groupsmentioning
confidence: 88%
“…When C is algebraically closed, Z(0)-exhaustion (and unicity) is in [39] and [40] when C = C and the arguments of [40] carry over to C; exhaustivity was implicit in [53], and is established by Fintzen at the end of [24] (the hypothesis on G of [24] plays not role for level 0 representations).…”
Section: Corollary 325 Assume That Ind Gmentioning
confidence: 99%
“…(G n ) x,rn/2 (G n+1 ) x,0+ inflating the representation ρ of (G n+1 ) [x] . In ( [24], §2.4), J is denoted by K and λ 0 is still denoted by ρ. To describe the representation κ of K we introduce more notations following ([24] 2.5).…”
Section: Types à La Bushnell-kutzkomentioning
confidence: 99%
See 1 more Smart Citation